A case study of stakeholder perceptions on communicative competence in engineering technical oral presentation / E. Bhattacharyya - Bhattacharyya , E. (2014)

(untitled)
To date, the notion of communicative competence is deemed “fuzzy” and limited in its operational definition from a linguistic and rhetorical perspective in oral communication literature. An understanding of communicative competence requirements in technical oral presentations stems from the lack of linguistic and rhetorical competency studies required among ESL learners in a Malaysian setting; employer discontent over graduates’ apparent lack of communication skills and limited literature on linguistic and rhetorical features necessary in scientific and engineering oral presentations (Dannels, 2009; Hafizoah Kassim & Kassim Ali 2010; Morton, 2009). The notion becomes more complex when selected stakeholders from various communities of practice (COP) are required to provide their perceptions on such a notion in a workplace related communicative event, the technical oral presentation. Technical oral presentations are project presentations delivered by final year engineering students to a panel of examiners comprising selected members from the academic and professional engineering community. Drawing on the theoretical principles of communicative competence, this study initially investigates the notion based on five sub-sets of communicative competence constructs namely strategic, socio-cultural, interactional, linguistic and discourse competence. In this study, these sub-sets are termed as presentation skills and attribute construct (strategic and socio-cultural competence), behavioral skills and attribute construct (strategic and interactional competence), content construct (linguistic and discourse competence), language competency construct (linguistic competence) and non-verbal skills construct (interactional competence). The notion is further investigated within critique sessions of technical oral presentations from the linguistic and rhetorical dimension as used by ESL learners in a Malaysian setting, an area deemed lacking in scientific and engineering technical oral presentations iv in the Malaysian setting. A mixed methods design (which encompassed two phases) was utilised. In the quantitative phase, 240 final year engineering students (as participants from the academic community) and 66 engineers (from the professional engineering community) who as end users of the said communicative event, were required to respond to a questionnaire based on the above mentioned constructs. The analysis revealed that there are no significant findings except for the content construct (introduction stage). Inferential tests however, revealed that slight differences exist on the level of importance accorded to various items listed within each construct. The interpretive stage necessitated selected members of the academia (26 students; 13 lecturers; and 6 language lecturers) and 12 engineers from the professional engineering community to comment on linguistic and rhetorical features considered necessary to create that “magic” or “interaction and engagement” in critique sessions within technical oral presentations. Thematic analysis revealed the prevalence of five linguistic (technical competence, disciplinary competence, meta-cognitive competence, linguistic competence, and structural competence) and two rhetorical (rhetorical competence and interpersonal and interactive competence) themes. This study addresses the linguistic and rhetorical competence required of ESL engineering students as perceived by ESL practitioners in the Malaysian tertiary education setting as well as those from the science and engineering profession. A suggested linguistic and rhetorical framework is proposed in an attempt to enhance the communicative competence requirement in critique sessions within technical oral presentations to enable today’s ESL graduates to speak like engineers in tomorrow’s future.